Accessibility and opportunities in tertiary education : borderless and 'Pedalaman'. - Alias Mohd Yatim (2008)
Currently, the infrastructure in much of East Malaysia and eastern coast of Peninsular Malaysia are still relatively undeveloped as compared to most part of Malaysia.